Study on the manufacturing processes of aspheric glass lens - Chan, Yi Yan. (2008)
This report looks into the possibilities of process characterization and modification to reduce the high defects.A brief introduction of the manufacturing of glass balls is presented. The emphasis of the report will be in the diamond grinding, lapping and polishing processes.